Immunogenicity of three recombinant hepatitis B vaccines administered to students in three doses containing half the antigen amount routinely used for adult vaccination - Baldy José Luís da Silveira; Lima Gerson Zanetta de; Morimoto Helena Kaminami; Reiche Edna Maria Vissoci; Matsuo Tiemi; Mattos Edlivia Dias de; Sudan Luci Cristina Pulga (Universidade de São Paulo (USP), 2004)
We evaluated the immunogenicity of three recombinant hepatitis B vaccines, one Brazilian (Butang, Instituto Butantan) and two Korean vaccines (Euvax-B, LG Chemical Ltd. and Hepavax-Gene, Greencross Vaccine Corp.), administered intramuscularly to students aged 17 to 19 years in three 10-µg doses (corresponding to half the amount of antigen routinely used for adult vaccination) at intervals of one month between the first and second dose, and of four months between the second and third dose. A total of 316 students non-reactive for any serological marker of hepatitis B virus infection were vaccinated: 77 (24.4%) with the Butang vaccine, 71 (22.5%) with Euvax-B, 85 (26.9%) with Hepavax-Gene and, for comparison, 83 (26.2%) with Engerix-B (GlaxoSmithKline), whose efficacy in young adults at the dose used here has been confirmed in previous studies. Similar seroconversion rates (anti-HBs > 10 mIU/mL about one month after application of the third dose) were obtained for the Butang, Euvax-B, Hepavax-Gene and Engerix-B vaccines (96.2%, 98.6%, 96.5% and 97.6%, respectively). The frequency of good responders (anti-HBs > 100 mIU/mL) was also similar among students receiving the four vaccines (85.8%, 91.6%, 89.4% and 89.2%, respectively). The geometric mean titers (GMT) of anti-HBs about one month after the third dose obtained with these vaccines were 727.78 ± 6.46 mIU/mL, 2009.09 ± 7.16 mIU/mL, 1729.82 ± 8.85 mIU/mL and 2070.14 ± 11.69 mIU/mL, respectively. The GMT of anti-HBs induced by the Euvax-B and Engerix-B vaccines were higher than those obtained with the Butang vaccine (p < 0.05); this difference was not significant when comparing the other vaccines two-by-two. No spontaneous adverse effects attributable to the application of any dose of the four vaccines were reported.